COVID‐19 and ENT SLT services, workforce and research in the UK: A discussion paper. Issue 5 (8th August 2020) - Patterson, Joanne M; Govender, Roganie; Roe, Justin; Clunie, Gemma; Murphy, Jennifer; Brady, Grainne; Haines, Jemma; White, Anna; Carding, Paul
Abstract: Background: The COVID‐19 pandemic and the UK government's subsequent coronavirus action plan have fundamentally impacted on every aspect of healthcare. One area that is severely affected is ear, nose and throat (ENT)/laryngology where speech and language therapists (SLTs) engage in a diverse range of practice with patients with a range of conditions, including voice disorders, airway problems, and head and neck cancers (HNCs). A large majority of these patients are in high‐risk categories, and many specialized clinical practices are vulnerable. In addition, workforce and research issues are challenged in both the immediate context and the future. Aims: To discuss the threats and opportunities from the COVID‐19 pandemic for SLTs in ENT/laryngology with specific reference to clinical practice, workforce and research leadership. Methods & Procedures: The relevant sections of the World Health Organisation's (WHO) health systems building blocks framework (2007) were used to structure the study. Expert agreement was determined by an iterative process of multiple‐group discussions, the use of all recent relevant policy documentation, and other literature and shared documentation/writing. The final paper was verified and agreed by all authors. Main Contribution: The main threats to ENT/laryngology SLT clinical services include increased patient complexity related to COVID‐19 voice and airway problems, delayed HNC diagnosis, reduced access to instrumental procedures and inequitable care provision. The main clinical opportunities include the potential for new modes of service delivery and collaborations, and harnessing SLT expertise in non‐instrumental assessment. There are several workforce issues, including redeployment (and impact on current services), training implications and psychological impact on staff. Workforce opportunities exist for service innovation and potential extended ENT/SLT practice roles. Research is threatened by a reduction in immediate funding calls and high competition. Current research is affected by very limited access to participants and the ability to conduct face‐to‐face and instrumental assessments. However, research opportunities may result in greater collaboration, and changes in service delivery necessitate robust investigation and evaluation. A new national set of research priorities is likely to emerge. Conclusions & Implications: The immediate impact of the pandemic has resulted in major disruption to all aspects of clinical delivery, workforce and research for ENT/laryngology SLT. It is unclear when any of these areas will resume operations and whether permanent changes to clinical practice, professional remits and research priorities will follow. However, significant opportunity exists in the post‐COVID era to re‐evaluate current practice, embrace opportunities and evaluate new ways of working. What this paper adds What is already known on the subject: ENT/laryngology SLTs manage patients with a range of conditions, including voice disorders, airway problems and HNCs. The diverse scope of clinical practice involves highly specialized assessment and treatment practices in patients in high‐risk categories. A large majority of active research projects in this field are patient focused and involve instrumental assessment. The COVID‐19 pandemic has created both opportunities and threats for ENT SLT clinical services, workforce and research. What this paper adds to existing knowledge: This study provides a discussion of the threats and opportunities from the COVID‐19 pandemic for ENT/laryngology SLT with specific reference to clinical practice, workforce and research leadership. What are the potential or actual clinical implications of this work?: The COVID‐19 pandemic has resulted in major disruption to all aspects of clinical delivery, workforce and research for ENT/laryngology SLT. Changes to clinical practice, professional remits and research priorities are of indeterminant duration at this time, and some components could be permanent. Significant clinical practice, workforce and research opportunities may exist in the post‐COVID era.